Upaya Meningkatkan Minat Baca Siswa Sekolah Dasar dengan Menggunakan Media Gambar - Safira, Utin Trisna; Purnomo, Heru; Kurniawati, Wahyu (Universitas Muhammadiyah Magelang, 2025)
The aim of this research is to identify several approaches that can arouse children's interest in reading, especially elementary school students. For students in particular, interest in reading is something that is very important. It is a collective obligation for parents, teachers and elementary school children to try to arouse interest in reading. As a result, one of the problems is the decline in students' enthusiasm for reading in class. Another problem is students' lack of interest in reading and teachers' indifference to the fact that students read books as part of their education. When trying to use image media to increase elementary school students' interest or willingness to read, it is best to provide encouragement and assistance to the students.